Revisiting the threshold effect of corruption in the link between public debt and economic growth in Nigeria - Eyitayo Oyewunmi Ogbaro; Ademola Obafemi Young; Rebecca Folake Bank-Ola (Economic Journal of Emerging Markets, 2022)
Purpose ― This study contributes to the empirical literature on the nonlinear relationship between public debt and economic growth in Nigeria using threshold regression methodology. It provides insight into how Nigeria can grow out of debt sustainably in the face of the prevailing level of corruption as an institutional indicator. Method ― Stata's threshold command is used for data analysis, and this command fits time-series threshold models in finding the optimal number of thresholds. It does this by minimising an information criterion and using conditional least squares to estimate the parameters of the threshold regression model. Findings ― The results show that the relationship between public debt and economic growth is nonlinear. The threshold effect of public debt on growth depends on the debt-to-GDP ratio and the level of corruption. Substantial evidence supports two threshold levels of debt-to-GDP ratio and corruption in the debt-growth nexus. The two threshold levels of corruption are 63.21 and 64.27 (on a scale of 0 to 100), with the growth effect of public debt being positive and significant in the second regime only. Implication ― Public debt exerts significant positive effects on growth as long as corruption is kept at a moderate level. Thus, the government of Nigeria needs to ensure that corruption is pegged at a fairly moderate level that will guarantee the positive contribution of accumulated debt to economic growth. Originality ― Unlike previous works, the study addresses the problem caused by the mechanical effect of a change in the real GDP growth rate on debt. It is based on the assumption of a maximum of two thresholds.